A study of the effectiveness analysis for survivability of a surface warship from a torpedo attack. Issue 4 (2nd October 2019) - Cho, Hyunjin; Shin, Myoungin; Lee, Jinho; Kim, Wan-Jin; Kim, Woo Shik; Hong, Wooyoung
ABSTRACT: We design a simulator in order to seek a surface warship's survivability against a torpedo attack using MATLAB GUI. Assuming that a torpedo chases a warship in an acoustic-homing way, we model its mobility and detection mechanism according to passive sonar equation. A surface warship manoeuvres into a specified evasive course while deploying static and mobile decoys when a torpedo is detected. Taking a warship's survival probability as a measure of effectiveness, we perform Monte Carlo simulation by changing four main factors, which include the decoy deployment plan, the torpedo's initial location, the torpedo's maximum target detection range, and the mobile decoy's speed. The simulation results show that using both mobile decoys and static decoys guarantees a higher survival probability than using only static decoys, which depends on their deployment locations and speeds. We further investigate which factors are more likely to affect the survivability via regression analysis, which was based on the simulation results. The regression model results show that torpedo's detection ability and the speed of mobile decoys highly affect the warship's survival probability.